Assessing design principles for climate services training courses: educational design principles assessment of six C3S Blended Training courses within the Copernicus Climate Change Service. Issue 5 (28th March 2022) - del Pozo, Maria; Gulikers, Judith; van Slobbe, Erik; den Brok, Perry; Ludwig, Fulco
Abstract: The current climate service creation practice misses clear provider–user collaborations, and this presents a challenge for the educational design of capacity-building programs. This study analyses the formation of educational principles in six training courses aimed at tailored climate services. The design principles are analyzed using the constructive alignment and three curriculum perspectives as analytical frameworks. Three main issues were identified: overambitious one-size-fits-all learning goals; the role of a case study in overcoming the lack of knowledge and skills; and ambiguity in assessments. These issues guided the implementation for improvements in the courses and need to be addressed in creation processes for user-tailored climate services in general by the wide community of climate service providers and users. Our findings reflect the tendency to insufficiently involve users in the creation of climate services and in capacity building more specifically. Although we use examples in the water sector and link them to collaborative processes in water governance, our findings potentially have implications for other sectors where collaboration between users and providers is needed as well. It also highlights not only the usefulness of educational and pedagogical disciplines as a pillar of capacity building but also their active inclusion in the design and implementation of climate services. HIGHLIGHTS: Understanding the nature of tailored climate services is the first step into introducing its characteristics into design principles for capacity building. Including collaborative and transdisciplinary processes in capacity building programs potentially supports development of tailored climate services. Producers and users are very heterogeneous, and there is a need to further understand them in order to develop a tailored capacity building.